Interactive Media BELBICAR (Belajar Bilangan Cacah Ribuan) Based on HTML5 Using Articulate Storyline 3 for Participants in Grade III Elementary School - Cempa Huzaimah; Yuniawatika; Ni Luh Sakinah Nuraini (LPPM Undiksha, 2025)
Students’ difficulties in understanding mathematical concepts are largely caused by the suboptimal use of relevant learning media to visualize abstract material. This study aims to develop an interactive learning medium, BELBICAR (Belajar Bilangan Ribuan), based on HTML5 using Articulate Storyline 3 for third-grade elementary school students. The research employed a Research and Development (R&D) approach based on the ADDIE model, which consists of the stages of Analyze, Design, Development, Implementation, and Evaluation. The effectiveness of the BELBICAR interactive media was analyzed using the normalized gain (n-gain) based on pre-test and post-test data collected from 28 third-grade students. The results showed that the average score of material validation reached 91.66%, categorized as very valid, while the average score of media validation was 93.75%, also categorized as very valid. In addition, the BELBICAR interactive media obtained practicality scores of 96.12% from teachers and 95.85% from students, both categorized as very practical. The media achieved an n-gain score of 75.83, which falls into the high category, indicating that the BELBICAR interactive media is highly effective. It can be concluded that the HTML5-based BELBICAR interactive media developed using Articulate Storyline 3 is capable of visualizing integer concepts in the thousands, thereby leading to high student learning outcomes. However, a limitation of the BELBICAR media lies in the restricted scope of its content, which is limited to the formulated learning objectives. Therefore, additional learning activities, such as student worksheets (LKPD), are recommended to maximize students’ understanding of integers in the thousands through the use of this media.